2020
DOI: 10.1016/j.promfg.2020.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of In Situ Zn-TiB2 Nanocomposite

Abstract: Zinc (Zn) matrix composite has been newly discovered categories of biodegradable materials. With a combination of chemical stability, thermal stability and biocompatibility, ceramic nanoparticles outperformed intermetallics of zinc alloys with inherent advantages of retaining a proper corrosion rate and an exceptional ductility. Compared with Zn alloys, Zn matrix nanocomposites showed an unprecedented strengthening without sacrifices of corrosion rate, which were introduced by intermetallics. In this work, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Corrosion test results confirmed that the suitable CR of Zn–2Fe was not impacted by the addition of WC nanoparticles [ 308 ]. Recently, Guan et al [ 309 ] fabricated Zn–3TiB 2 nanocomposite via ultrasound processing and hot rolling. With 3 vol% TiB 2 nanoparticles, the mechanical strength of zinc has been significantly enhanced, e.g., H, σ TYS and σ UTS , by 85, 90 and 45%, respectively, while ε retained 23% indicating the it as promising candidate for biodegradable medical devices.…”
Section: Zn-based Compositesmentioning
confidence: 99%
“…Corrosion test results confirmed that the suitable CR of Zn–2Fe was not impacted by the addition of WC nanoparticles [ 308 ]. Recently, Guan et al [ 309 ] fabricated Zn–3TiB 2 nanocomposite via ultrasound processing and hot rolling. With 3 vol% TiB 2 nanoparticles, the mechanical strength of zinc has been significantly enhanced, e.g., H, σ TYS and σ UTS , by 85, 90 and 45%, respectively, while ε retained 23% indicating the it as promising candidate for biodegradable medical devices.…”
Section: Zn-based Compositesmentioning
confidence: 99%
“…In recent years, many alloys or composites of Zn-based biodegradable materials have been established with improved biocompatibility, bio-corrosion, and mechanical properties [ 59 , 60 , 61 , 62 , 63 ]. Many essential trace elements for the human body have been used for making Zn-based biodegradable alloys, and many types of reinforcement materials have been used for making Zn composites [ 64 , 65 , 66 , 67 ]. Among these reinforcements, calcium phosphate-based reinforcements are the most widely used [ 41 ].…”
Section: Zn-based Biomaterialsmentioning
confidence: 99%
“…Similarly, the addition of nano‐SiC (up to 2.0 wt%) into Zn matrices gradually increased the σ CYS, MH, DR, and cell viability (CV); however, higher concentrations (3 wt%) significantly decreased the σ CYS due to the aggregation of nano‐SiC in the Zn matrix. [ 49 ] In another study, [ 50 ] the positive impact of titanium diboride (≈3 vol%) addition in pure Zn was reported with improvement in MH by 85%, σ YS by 90%, and σ UTS by 45%. It can be seen that the mechanical properties of the composites reinforced with these materials (except TCP) still did not meet the benchmark values ( σ YS : 200–230 MPa and σ UTS : 300 MPa) for load‐bearing bone implant.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42,43 ] Zn‐based MMCs are usually reinforced with bio‐ceramics, such as hydroxyapatite, [ 44,45 ] tricalcium phosphate (TCP), [ 46 ] tungsten carbide, [ 47 ] monetite, [ 48 ] silicon carbide (SiC), [ 49 ] and titanium diboride. [ 50 ] Yang et al [ 44 ] reported a reduction in ultimate compressive strength ( σ UCS ), while improvement in biocompatibility upon the addition of hydroxyapatite in pure Zn. Lu et al [ 39 ] reported that the addition of 1 vol% β‐ TCP in a Zn–Mg alloy system remarkably increased its σ YS (≈10%), σ UTS (≈10%), and elongation ( ε ; ≈102%), while exhibiting a suitable DR (0.046 mm y −1 ).…”
Section: Introductionmentioning
confidence: 99%